An Overview of Innovative Techniques to Improve Cervical Cancer Screening - Esther R. Nijhuis; Nathalie Reesink-Peters; G. Bea A. Wisman; Hans W. Nijman; Jelmer van Zanden; Haukeline Volders; Harry Hollema; Albert J. H. Suurmeijer; Ed Schuuring; Ate G. J. van der Zee (Cellular Oncology)
Although current cytomorphology-based cervical cancer screening has reduced the incidence of cervical cancer, Papsmears are associated with high false positive and false negative rates. This has spurred the search for new technologies to improve current screening. New methodologies are automation of Pap-smear analysis, addition of new biological or molecular markers to traditional cytology or using these new markers to replace the current screening method. In this overview we will summarize data on cervical cancer epidemiology and etiology and the current cervical cancer screening approach. Available data on new screening approaches, such as quantitative cytochemistry, detection of loss of heterozygosity (LOH) and hypermethylation analysis will be reviewed.We discuss the potential of these approaches to replace or augment current screening. When available, data on cost– effectiveness of certain approaches will be provided. In short, Human Papillomavirus (HPV) DNA detection stands closest to implementation in nation-wide screening programs of all markers reviewed. However, specificity is low in women aged <35 years and the psychological effects of knowledge of HPV positivity in absence of cervical (pre) malignant disease are important drawbacks. In our opinion the results of large clinical trials should be awaited before proceeding to implement HPV DNA detection. New technologies based on molecular changes associated with cervical carcinogenesis might result in comparable sensitivity, but improved specificity. Hypermethylation analysis is likely to be more objective to identify patients with high grade squamous intra-epithelial lesions (HSIL) or invasive cancer with a higher specificity than current cytomorphology based screening.